The Effect Of Information Technology Utilization, Audit Quality, nd Monitoring On The Quality Of Financial Statements - Rusli, Andika; Mutmainna, Mutmainna; Sari, Nispa (Review of Accounting and Taxation, 2024)
Abstract Purpose - TThis study aims to analyze the influence of information technology utilization, audit quality, and supervision on the quality of financial statements at the Palopo City Inspectorate Office. Design/methodology/approach - he research method used is quantitative with multiple linear regression techniques. The research sample is 40 auditors at the Palopo City Inspectorate Office in 2022. Finding - The results of the study show that the use of information technology and audit quality do not have a positive and significant effect on the quality of financial statements, in contrast to the quality of audit and supervision which produces a significant influence. Meanwhile, supervision does not have a significant effect on the quality of financial statements. The use of information technology can increase the efficiency and effectiveness of the audit process, thereby improving the quality of audits. Originality - Good audit quality can increase confidence in audit findings, thereby improving the quality of financial statements. This study recommends that the Palopo City Inspectorate Office increase the use of information technology and audit quality to improve the quality of financial reports.